Two Strains of Lactobacilli Effectively Decrease the Colonization of VRE in a Mouse Model - Li, Xianping; Song, Liqiong; Zhu, Siyi; Xiao, Yuchun; Huang, Yuanming; Hua, Yuting; Chu, Qiongfang; Ren, Zhihong (Frontiers in Cellular and Infection Microbiology, 2019)
Vancomycin-resistant Enterococcus (VRE) infection is a serious challenge in clinic and there are no effective treatments at present. Fecal microbiota transplantation (FMT) and probiotic intervention are shown to be a promising approach in reducing the colonization of certain pathogenic bacteria in gastrointestinal tract, however, such information is lacking about VRE. Thus, in this study, we evaluated effect of Lactobacillus murinus Y74 and Lactobacillus plantarums HT121 on the colonization of VRE in a mouse model. We found that both lactobacilli rapidly reduced the VRE colonization. Results of fecal microbiota composition and mRNA expression in the colonic tissue further showed that mice in both FMT and the two lactobacilli treatment groups restored their intestinal microbiota diversity faster than those in the PBS-treated control group. While administration of lactobacilli helped restore Firmicutes Phylum to the normal level more quickly compared to FMT or PBS treatment, it promoted restoration of Bacteroides Phylum to normal level less quickly than did FMT. Furthermore, these treatments differentially impacted the relative abundance of intestinal microbiota composition at the levels of phylum, class, order, family, genus, and species. Results of RNA-seq showed that FMT treatment induced more genes expression in colon compared to lactobacilli treatment. Defense-related genes such as defensin α, Apoa1, and RegIII were down-regulated in both FMT and the two lactobacilli treatment groups. Together, our findings indicate that two strains of lactobacilli and FMT treatment are all effective in decreasing the colonization of VRE; however, their working mechanisms might be different, which should be investigated in the future studies.